Early diagenetic minerals and variables influencing their distributions in two long cores (>40m), Mississippi River delta plain - Bailey, A. M.; Roberts, H. H.; Blackson, J. M. (Journal of Sedimentary Research, 1998)
Two long (>40 m) continuous push cores of sediments from the Mississippi Delta Plain, one at a northern freshwater site and one at a southern marine-influenced site, have provided samples of individual concretions and homogenized bulk samples for a study of early diagenesis. Early (<10,000 y) diagenetic minerals are abundant and include: siderite>pyrite>calcite nearly equal dolomite>vivianite approximately hematite. Siderite formed postburial and contains bands of clastic minerals and accessory diagenetic calcite and dolomite, as well as Ca, Mg, and Mn substituted in the lattice. Values for delta 13 C increase with increasing depth to +11 per mil (PDB) at a depth of 40 m, reflecting the increasing role of methanogenesis with depth. From analyses of bulk samples, pyrite concentrations are higher in organic-rich horizons, do not vary appreciably with depth below one meter when adjusted for organic-carbon control, and are generally higher in the marine-influenced core than at the freshwater site. Conversely, concentrations of siderite are higher in fine-grained siliciclastic horizons, increase with depth to about 20 m, and do not vary with the extent of marine influence in these cores. To a first approximation, distributions of pyrite appear to be controlled by variations in organic carbon concentration in sulfate-sufficient systems that formed through marine incursion into organic-rich layers that cap sediment packages in the deltaic system. Residual pyritic S is sulfate-controlled and lower in the northern, more freshwater organic-rich sediments. Siderite formation appears to be focused in sulfate-deficient systems that formed when siliciclastic wedges that constitute the central parts of sediment packages prograded into lacustrine or bay environments. Low sulfate levels in these horizons in both cores facilitated similar levels of siderite. A juxtaposition of marine versus freshwater diagenetic mineral suites in adjacent horizons resulted from these interactions between physical and geochemical processes.
id: 5